(untitled) (London Journal of Medical and Health Research, 2025)
RNase P ribozymes, derived from the M1 RNA of Escherichiacoli, have shown great promise as a novel nucleic acid-based gene interference approach to modulate gene expression. When the M1 RNA component of RNase P is covalently linked with a guide sequence (GS), it can be engineered into a sequence-specific endonuclease M1GS ribozyme. As the GS base-pairs with target mRNAs, it forms a structure that mimics a pre-tRNA-like substrate, allowing for M1 RNA’s structure-based recognition mechanism. These M1GS constructs function catalytically and irreversibly, capable of cleaving target mRNA substrates without relying on host proteins. M1GS activity enhancement has been achieved through an in vitro selection process that introduced mutations in the catalytic core of M1 RNA. This process generated ribozyme variants with greatly improved cleavage efficiency and substrate affinity. M1GS ribozymes have been successful in inhibiting herpes simplex virus 1 (HSV-1) by targeting genes critical for viral infection. HSV-1 is the causative agent of cold sores and may lead to severe morbidity and mortality in neonates and immunocompromised individuals. HSV-1 establishes lifelong latent infection, and novel anti-HSV-1 strategies are needed to block and eliminate viral latency and reactivation. Using HSV-1 infection as an example, this review will summarize the function of RNase P and its catalytic RNA, the enhancement and engineering of M1GS ribozymes, and their potential as a gene-targeting agent for therapeutic applications against HSV-1.